Capital adequacy in the context of markets turmoil - Claudia Ioana Vlad; Ana-Maria Rada; Andreea-Florentina Rada (Romanian Journal of Fiscal Policy (RJFP), 2013)
Financial stability is the key objective that sustains and empowers investments and economic groth, or scatters the opportunities when lacking. As growth translates to profitability, and profitability is dependent upon solvalibility, the need for a deep knowledge of all potential risks surfaces. This scope is seeken through all the reglementations of the financial markets. Since the last major financial crisis had a less devastating impact on the insurance market and the losses suffered by the insurance companies were smaller than the losses of banks, we will focus on the risk valuation apllied by these insurance companies. The proper valuation of risks is mirrored in the Solvency Capital Requirement calculated,which under Solvency II framework,corresponds to Value-at-Risk of the basic own funds subjected to a confidence level of 99.5% over a one-year period.
Keywords: G22; G28; 330; Financial stability; Insurance market; Solvency Capital Requirement; Risk measurement; Value-at-Risk